Identification of Aspergillus and Mucorales in formalin-fixed, paraffin-embedded tissue samples: Comparison of specific and broad-range fungal qPCR assays. (19th June 2018) - Springer, J; McCormick Smith, I; Hartmann, S; Winkelmann, R; Wilmes, D; Cornely, O; Kessel, J; Löffler, J; Rickerts, V
Abstract: Establishing the etiology of invasive fungal infections is important to guide therapeutic options and for epidemiologic purposes. Formalin-fixed, paraffin-embedded (FFPE) tissue specimens from patients with proven invasive fungal infections are valuable to determine the etiology of systemic fungal infections. We compared different polymerase chain reaction (PCR) amplification strategies from FFPE tissue blocks to identify agents of invasive fungal infections. We found that specific PCR assays show superior sensitivity in the identification of DNA of Mucorales and Aspergillus and mixed infections caused by both as compared to broad-range PCR assays. Shorter amplicon lengths and less detection of contaminating fungal DNA are potential factors involved. However, detection of fungal DNA by highly sensitive specific PCR assays in the absence of demonstration of fungal elements in tissue suggests that PCR results should be interpreted in the context of the histopathology and clinical findings.